Productivity of Panicum maximum cv. Trichoglume As an Effect of Substitution Organic Fertilizer in The Second Cutting - A, Vino; Witariadi, N. M.; Candraasih, N. N. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This research is aimed to know the productivity of Panicum maximum cv.Trichoglume grass as the result of organic fertilizer substitution toward urea fertilizer on the second truncation. This research was done in Greenhouse of Sading Village, Mengwi district, Badung regency. This research was carried out for 8 weeks. The research design used was Completely Randomized Design, consisting of seven treatments and five repetitions. The treatments were: A = urea dose 200kg/ha; B= urea dose 150kg/ha +10 ton/ha cow’s bio slurry ; C = urea dose 100 kg/ha + 20 ton/ha cow’s bio slurry ; D = urea dose 50 kg/ha + 30 ton/ha cow’s bio slurry ; E = urea dose 150 kg/ha + 10 ton/ha pig’s bio slurry; F = urea dose 100 kg/ha + 20 ton/ha pig’s bio slurry; G = urea dose 50 kg/ha + 30 ton/ha pig’s bio slurry . Variables observed were the aspect of growth, production, and characteristics. The research findings revealed that variable of growth shows not significant different result (P> 0.05) but the amount of tillers on treatment A shows a significantly different result (P<0.05), the variable of production statistically shows significant different (P<0.05) on treatment D, the variable of growth shows significant different (P<0.05) toward treatment F and leaves’ area are significantly different (P<0.05) towards treatment D. According to these findings, it can be concluded that the substitution of urea fertilizer 50 kg/ha by adding 30 ton/ha pig’s bio slurry resulted on the highest productivity of Panicum maximum cvTrichoglume grass. Key words: Bio slurry, pig’s bio slurry , fertilizers, fertilizer’s dosage,  benggala grass